The Challenges of The Implementation of Smart Contracts Related to Consumer Protection in Electronic Transactions - Qur’ani Dewi Kusumawardani; Dina W Kariodimedjo (Faculty of Law, Universitas Pekalongan, 2022)
Smart contracts, which are computer code protocolsthat leverage digital contracts in the blockchainnetwork. Smart contracts can make transactions noteasy to change, more permanent, not easily damaged,more efficient, faster, and more secure becauseeverything is recorded in the blockchain system.However, smart contracts are not without challenges.This study uses a normative juridical approach byanalyzing secondary legal materials complemented byrelevant primary legal materials. Challenges related tosmart contracts in consumer protection, namelyprogramming codes, may not guarantee representationof the parties, the inability of smart contracts (to date)to provide flexibility in contractual frameworks, andcomplex programming languages for partiesunfamiliar with coding. In addition, the partiesinvolved in the transaction and do not have a codingbackground, of course, do not easily interpret smartcontracts. In the end, regulation is essential to protectusers, ensure the security and rights of the parties, sothat this technology does not disrupt particularmarkets, but on the other hand, too much regulationwill hinder innovation